2022
DOI: 10.3389/fpls.2022.935885
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing self-pollinated crop breeding employing genomic selection: From schemes to updating training sets

Abstract: Long-term breeding schemes using genomic selection (GS) can boost the response to selection per year. Although several studies have shown that GS delivers a higher response to selection, only a few analyze which stage GS produces better results and how to update the training population to maintain prediction accuracy. We used stochastic simulation to compare five GS breeding schemes in a self-pollinated long-term breeding program. Also, we evaluated four strategies, using distinct methods and sizes, to update … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…The realized genetic gains from GS‐enabled breeding programs were greater than those of a conventional breeding program. This finding was consistent with previous simulation studies in other crop species, including tea, rice, wheat, and sorghum (Lubanga et al., 2022; Muleta et al., 2019; Sabadin et al., 2022; Tessema et al., 2020), which affirmed that breeding programs implementing GS can achieve higher genetic gain than phenotypic selection breeding programs. These findings revealed that the use of the GS technique can enhance the efficiency of the breeding program even in the presence of G × E due to information sharing among genotyped clones over years and locations (Heffner et al., 2009).…”
Section: Discussionsupporting
confidence: 92%
“…The realized genetic gains from GS‐enabled breeding programs were greater than those of a conventional breeding program. This finding was consistent with previous simulation studies in other crop species, including tea, rice, wheat, and sorghum (Lubanga et al., 2022; Muleta et al., 2019; Sabadin et al., 2022; Tessema et al., 2020), which affirmed that breeding programs implementing GS can achieve higher genetic gain than phenotypic selection breeding programs. These findings revealed that the use of the GS technique can enhance the efficiency of the breeding program even in the presence of G × E due to information sharing among genotyped clones over years and locations (Heffner et al., 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Pea has limited genetic diversity (Yang et al, 2022) and presumably has Me less than the 500 random QTN selected in our study. This aligns with several simulation studies that predominantly assume polygenic traits are controlled by 500 or greater QTN (Wientjes et al, 2015;Yao et al, 2018;Peters et al, 2020;Sabadin et al, 2022).…”
Section: Founder Population and Genetic Parameterssupporting
confidence: 87%
“…Recently, Sabadin et al (2022) also emphasized the relationship between the number of parents and the effective population size ( N e ). In the simulation study, the author reported greater resilience to the loss of genetic variance over the long term, involving 48 parents compared to 24 parents.…”
Section: Discussionmentioning
confidence: 99%
“…In the To enhance the utility of predictions in earlier generations, studies should now assess the feasibility of genotyping greater numbers of plants, reducing generation time, and accelerating the average rate of genetic gain. While many studies have shown the benefits of reducing generation time in simulations (Bernardo, 2020;Sabadin et al, 2022), evaluation of real-world efficacy will rely on understanding the costs of restructuring breeding programmes to handle increased labour, the efficacy of within-family predictions using models trained on historic data, and increased genotyping costs associated with greater sampling. As lines are selected earlier in the breeding programme pipeline, a greater emphasis will be placed on withinfamily than among-family selection.…”
Section: Implementation Of Genomic Selection For Fhb Resistancementioning
confidence: 99%